Monoamine Oxidase is a Major Determinant of Redox Balance in Human Atrial Myocardium and is Associated With Postoperative Atrial Fibrillation. Issue 1 (26th February 2014) - Anderson, Ethan J.; Efird, Jimmy T.; Davies, Stephen W.; O'Neal, Wesley T.; Darden, Timothy M.; Thayne, Kathleen A.; Katunga, Lalage A.; Kindell, Linda C.; Ferguson, T. Bruce; Anderson, Curtis A.; Chitwood, W. Randolph; Koutlas, Theodore C.; et al.
Abstract : Background: Onset of postoperative atrial fibrillation (POAF) is a common and costly complication of heart surgery despite major improvements in surgical technique and quality of patient care. The etiology of POAF, and the ability of clinicians to identify and therapeutically target high‐risk patients, remains elusive. Methods and Results: Myocardial tissue dissected from right atrial appendage (RAA) was obtained from 244 patients undergoing cardiac surgery. Reactive oxygen species (ROS) generation from multiple sources was assessed in this tissue, along with total glutathione (GSHt) and its related enzymes GSH‐peroxidase (GPx) and GSH‐reductase (GR). Monoamine oxidase (MAO) and NADPH oxidase were observed to generate ROS at rates 10‐fold greater than intact, coupled mitochondria. POAF risk was significantly associated with MAO activity (Quartile 1 [Q1]: adjusted relative risk [ARR]=1.0; Q2: ARR=1.8, 95% confidence interval [CI]=0.84 to 4.0; Q3: ARR=2.1, 95% CI=0.99 to 4.3; Q4: ARR=3.8, 95% CI=1.9 to 7.5; adjusted P trend =0.009). In contrast, myocardial GSHt was inversely associated with POAF (Quartile 1 [Q1]: adjusted relative risk [ARR]=1.0; Q2: ARR=0.93, 95% confidence interval [CI]=0.60 to 1.4; Q3: ARR=0.62, 95% CI=0.36 to 1.1; Q4: ARR=0.56, 95% CI=0.34 to 0.93; adjusted P trend =0.014). GPx also was significantly associated with POAF; however, a linear trend for risk was not observed across increasing levels of the enzyme. GR was not associated with POAF risk. Conclusions: Our results show that MAO is an important determinant of redox balance in human atrial myocardium, and that this enzyme, in addition to GSHt and GPx, is associated with an increased risk for POAF. Further investigation is needed to validate MAO as a predictive biomarker for POAF, and to explore this enzyme's potential role in arrhythmogenesis.